Modernizing Multilateralism and Markets - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank, addresses these topics: (i) looking back –to see ahead; (ii) transformation in the global political economy; (iii) storm clouds over multilateralism and markets; (iv) a new multilateral network for a new global economy; (v) a new steering group; (vi) the WTO and the global trading system; (vii) energy and climate change; and (viii) fragile states.